STUDENTS ACTIVITIES IN SOLVING MATHEMATICS VERBAL QUESTIONS BASED ON VAK LEARNIG STYLES - Nurul Hidayah (Universitas Negeri Makassar, 2015)
The purpose of this study is to determine the activities of students who have visual learning style, auditorial, and kinestetik in solving the problem of verbal mathematics.This research is descriptive-qualitative research. Researchers act as the main instrument assisted by interview guides as well as verbal tasks (about the story). The subjects of this study were three students of class VIII-F SMP Negeri 3 Sungguminasa, consisting of one SGBV, SGBA, and SGBK. Data were obtained from job-based interviews. Collected data is analyzed through three stages, namely reviewing data, reducing data, and presenting data. The results of the study generally show: 1) SGBV, SGBA, and SGBK through the three stages of thinking, that is understanding the problem, preparing the settlement plan and carry out the settlement 2) SGBV, SGBA, and SGBK thinking processes tend to be almost the same that is conceptual. 3) The behavior of SGBV, SGBA, and SGBK in solving verbal math problems (SVM) varies